2007
DOI: 10.1093/ps/86.5.869
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Molting Method and Dietary Energy on Postmolt Performance, Egg Components, Egg Solid, and Egg Quality in Bovans White and Dekalb White Hens During Second Cycle Phases Two and Three

Abstract: Two experiments of 4 x 2 x 2 factorial arrangements of 4 dietary energy levels, 2 molting methods (feed withdrawal and no salt diet), and 2 strains (Bovans White and Dekalb White) were conducted to determine the effect of dietary energy and molting method on long-term postmolt performance of 2 strains of commercial Leghorns. In experiments 1 and 2, Bovans White hens (n = 576) and Dekalb White hens (n = 576) were randomly divided into 16 treatments (6 replicates of 12 birds per treatment). Experiment 1 lasted f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 33 publications
1
3
0
2
Order By: Relevance
“…However, approaching 100 weeks, there was a significant reduction on performance and egg quality. Normally, the molt procedure cause a significant increase on performance and egg quality at shortterm and these indexes tend to decrease according to the age of the bird due to the natural wear caused by constant egg production in industrial scale (Wu et al, 2007). Physiologically, there are great wear on oviduct tissues, and difficulty to absorb the nutrients and its transfer to the egg's composition (Newman and Lesson, 1999;Bar et al, 2001;Heflin et al, 2018;Elhamouly et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, approaching 100 weeks, there was a significant reduction on performance and egg quality. Normally, the molt procedure cause a significant increase on performance and egg quality at shortterm and these indexes tend to decrease according to the age of the bird due to the natural wear caused by constant egg production in industrial scale (Wu et al, 2007). Physiologically, there are great wear on oviduct tissues, and difficulty to absorb the nutrients and its transfer to the egg's composition (Newman and Lesson, 1999;Bar et al, 2001;Heflin et al, 2018;Elhamouly et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Different strains may to present different responses on performance after molt, especially on laying hens and semi-heavy hens (Said et al, 1984;Gongruttananun et al, 2017;Hu et al, 2019). There is very limited literature about the performance, egg composition, egg solids, egg quality, and profits of postmolt hens (Wu et al, 2007), especially at long-term, a period near or exceeding to 100 weeks. An induced molting not only may improve performance and eggshell quality, but also increase profits by optimizing the use of replacement pullets on commercial layer farms (Lee, 1982;Barker et al, 1981;Bell, 2003;Mazzuco et al, 2011;Gongruttananun, 2018) proving the importance to understand its effect at long-term.…”
Section: Discussionmentioning
confidence: 99%
“…La variable peso del huevo indicó que el peso del huevo no depende de la edad, ya que en condiciones normales, el tamaño y el peso del huevo tienden a aumentar después del pico de producción, debido al incremento del peso corporal del ave y la disminución en el nivel de producción (5,8,22). Todos los pesos obtenidos en el experimento fueron mayores a los datos reportados en la guía de manejo de la línea para las mismas edades (17), lo que confirma lo propuesto por Flemming(22) y Webster (20), quienes afirmaron que una de las ventajas de la utilización del DO es el aumento en el tamaño del huevo postmuda (Tabla 2).…”
Section: Discussionunclassified
“…Con respecto al cese de la producción, se ha considerado necesario para la regeneración del aparato genital (4,7) y rejuvenecimiento de la zona reproductiva (8)(9)(10), permitiendo la recuperación en el nivel productivo, no tan alto como el ciclo anterior, pero con un peso de huevo promedio mayor y una calidad de cáscara óptima (3,5,11). En resumen, la técnica del DO se utiliza para ayudar a manejar y sincronizar los ciclos de la producción de un lote de aves (1,2,); debido a que durante la muda suspenden la producción de huevos, pero luego de ser nuevamente estimuladas, retornan a la producción igualando o superando la respuesta productiva antes del estimulo inductor del cese productivo, este segundo ciclo puede durar entre 25 a 35 semanas (11,12).…”
Section: Introductionunclassified
“…In contrast, Harms et al (2000), Wu et al (2007), and Bouvarel et al (2010) reported that egg weight increased as the AMEn content of the diet increased. Under practical conditions, egg size depends primarily of the methionine, fat, and linoleic acid content of the diet (Safaa et al, 2008b).…”
Section: Hen Productivity and Egg Qualitymentioning
confidence: 95%